ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN (STUDI KASUS PADA KOPERASI PEGAWAI REPUBLIK INDONESIA UNIVERSITAS SLAMET RIYADI SURAKARTA) - Suprayitno Erni Widajanti (Universitas Slamet Riyadi, 2018)
So that the financial statements could be used as a basis for the assessment by themanagement, these financial statements should be analyzed further by the method ortechnique specific analysis. By using financial ratio analysis, it can be seen whether ornot healthy financial condition of a cooperative. Ratios are grouped in the ratio ofliquidity, solvency and profitability were able to describe the health condition of acooperative. Benchmark of health cooperatives under Decree of the State Minister ofCooperatives and Small and Medium No: 129 / KEP / M / KUKM / XI / 2002. Thecalculation result Liquidity (Current ratio) year from 2012 to 2014, in the category ofPretty Good Value. Solvency (Leverage Analysis):(less good) and Total Debt toequity ratio (Very Good). Return on Assets (ROA); (Classification Fair), Equityanalysis (Classification Good).Keywords: Liquidity, Solvency, Profitability, Performance